2021
DOI: 10.3389/fmars.2021.779283
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variability in Acoustic Behavior of Snapping Shrimp in the East China Sea and Its Correlation With Ocean Environments

Abstract: The snapping shrimp sound is known to be a major biological noise source of ocean soundscapes in coastal shallow waters of low and mid-latitudes where sunlight reaches. Several studies have been conducted to understand the activity of snapping shrimp through comparison with surrounding environmental factors. In this paper, we report the analysis of the sound produced by snapping shrimp inhabiting an area where sunlight rarely reaches. The acoustic measurements were taken in May 2015 using two 16-channel vertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…In a previous study on the correlation between underwater noise and sea level at Ieodo, the underwater noise also changed according to the tidal change and the phase of the moon [37]. Although the study of prawns conducted in the same sea area did not show circadian characteristics, the snap rate of prawns changed according to the tidal change (Table 2) [31]. According to the soundscape for various fish species such as Miichthys miiuy (brown croaker) and Lophius piscatorius (angler), there was a noticeable change with the tide but not with the moon phase.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In a previous study on the correlation between underwater noise and sea level at Ieodo, the underwater noise also changed according to the tidal change and the phase of the moon [37]. Although the study of prawns conducted in the same sea area did not show circadian characteristics, the snap rate of prawns changed according to the tidal change (Table 2) [31]. According to the soundscape for various fish species such as Miichthys miiuy (brown croaker) and Lophius piscatorius (angler), there was a noticeable change with the tide but not with the moon phase.…”
Section: Discussionmentioning
confidence: 90%
“…Unlike this study, the snap rate was quantitatively expressed by analyzing the data measured a short period at depths where visible light rarely enters. Although there is a seasonal difference in the measurement period in May, a snap rate of 200 to 1200 times occurred, and the snap rate changed according to the sea level [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Snapping shrimp typically live in dense aggregations hidden within the substrate of many coastal ecosystems (e.g., coral reef, sponges, rubble, oyster beds, rocky shores), together producing a continuous audible crackling sound (Johnson et al 1947;Mathews, 2007). Snapping shrimp acoustic activity is often the major determinant of ambient sound levels in coastal seas (Everest et al, 1948;Johnson et al, 1947;Lillis et al, 2014;Kaplan et al, 2015), and variation in snapping shrimp acoustic output has been found to account for much spatiotemporal soundscape variation, both in sound levels and frequency content, within temperate and tropical benthic marine ecosystems (Radford et al 2008;Radford et al 2010;Lillis et al 2014;Staaterman et al 2014;Butler et al 2017;Lee et al, 2021). This spatiotemporal variability of snapping shrimp sound production likely influence a range of acoustically-mediated animal activities, including navigation and habitat selection by settlement-stage fish and invertebrate larvae (Simpson et al, 2008;Lillis et al, 2013), and perhaps even functions as an auditory cue for migrating cetaceans to avoid rocky shorelines (Allen, 2013).…”
Section: Introductionmentioning
confidence: 99%